NĂNG LỰC HIỆN TẠI, THÁCH THỨC VÀ NHU CẦU NÂNG CAO NĂNG LỰC CỦA CÁN BỘ KHUYẾN NÔNG TRONG BỐI CẢNH BIẾN ĐỔI KHÍ HẬU TẠI TỈNH BẮC KẠN - Hoàng, Hương; Hà, Tuân; Phạm, Hương; Bế, Long; Vũ, Ánh; Hoàng , Ngân; Khuất, Huyền (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2024)
This study aims to assess the current capacity, challenges and needs of capacity building of agricultural extension workers in Bac Kan province under the context of climate change. The research was conducted during 2021-2022, using semi-structured questionnaires for face-to-face interviews with 17 leaders and 59 staff members of agricultural extension agencies in the province. Results show that the agricultural extension workforce of Bac Kan province has advantages in terms of qualifications and work experience. Nonetheless, they also encountered a number of challenges under the context of increasingly changing environment. These include: (1) passivity in guiding production and technical transfer activities, (2) difficulties in pest and disease forecast and management, (3) increased workload; and (4) their communication and/or community outreach activities face many challenges, especially in localities with ethnic minorities, scattered housing locations, and difficult travel access. Most of the agricultural extension workers have not been trained in both agricultural extension methods and climate change adaptation. Technical climate-resilient production manuals (for both crops and livestock), effective communication methods and information sharing networks among agricultural extension officers were considered the main learning resources that they desired to be equipped to effectively carry out their tasks under the context of climate change.